2008
DOI: 10.5194/bg-5-739-2008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of increased atmospheric CO<sub>2</sub> on small and intermediate sized osmotrophs during a nutrient induced phytoplankton bloom

Abstract: Abstract. We report the transient population dynamic response of the osmotrophic community initiated by a nutrient pulse in mesocosms exposed to different pCO 2 levels. Differences in phytoplankton and heterotrophic bacteria abundances associated with the CO 2 treatment are also described. Coastal seawater was enclosed in floating mesocosms (27 m 3 ) and nutrients were supplied initially in order to stimulate growth of microbial organisms, including the coccolitophorid Emiliania huxleyi. The mesocosms were mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
42
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 56 publications
6
42
3
Order By: Relevance
“…The subsequent decline in abundance was likely due to topdown control from the heterotrophic nanoflagellate community, which displayed an increase in abundance at this time (Hancock et al, 2017). Bacterial tolerance to high CO 2 has been reported previously in this region Westwood et al, 2018) and has also been reported in numerous studies in the Arctic (Grossart et al, 2006;Allgaier et al, 2008;Paulino et al, 2008;Baragi et al, 2015;Wang et al, 2016), suggesting that the marine bacterial community will be resilient to increasing CO 2 .…”
Section: Ocean Acidification Effects On Bacterial Productivitysupporting
confidence: 63%
See 2 more Smart Citations
“…The subsequent decline in abundance was likely due to topdown control from the heterotrophic nanoflagellate community, which displayed an increase in abundance at this time (Hancock et al, 2017). Bacterial tolerance to high CO 2 has been reported previously in this region Westwood et al, 2018) and has also been reported in numerous studies in the Arctic (Grossart et al, 2006;Allgaier et al, 2008;Paulino et al, 2008;Baragi et al, 2015;Wang et al, 2016), suggesting that the marine bacterial community will be resilient to increasing CO 2 .…”
Section: Ocean Acidification Effects On Bacterial Productivitysupporting
confidence: 63%
“…Kim et al, 2006;Hopkinson et al, 2010;Riebesell et al, 2013;Paul et al, 2015;Bach et al, 2016;Bunse et al, 2016). Studies in the Arctic reported increases in phytoplankton primary productivity, growth, and organic matter concentration at CO 2 levels ≥ 800 µatm under nutrient-replete conditions (Bellerby et al, 2008;Egge et al, 2009;Engel et al, 2013;Schulz et al, 2013), whilst the bacterial community was unaffected (Grossart et al, 2006;Allgaier et al, 2008;Paulino et al, 2008;Baragi et al, 2015). These studies also highlight the importance of nutrient availability in the community response to elevated CO 2 , with substantial differences in primary and bacterial productivity, chlorophyll a (Chl a), and elemental stoichiometry observed between nutrient-replete and nutrient-limited conditions Schulz et al, 2013;Sperling et al, 2013;Bach et al, 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The higher abundances of picophytoplankton I at high pCO 2 resulted thus from somewhat enhanced growth rates. Paulino et al (2008) reported an increased abundance of picophytoplankton in a high CO 2 mesocosm; however, this was towards the end of the experiment when all nutrients were depleted. During another Norwegian fjord mesocosm experiment, still nutrient-replete, the total number of small-sized picophytoplankton did not change under increased pCO 2 (750 µatm; Hopkins et al, 2010;Newbold et al, 2012).…”
Section: Phasementioning
confidence: 87%
“…Effects on other bacterioplankton activities and overall performance have been found to be more variable between experiments. While for one in situ mesocosm experiment at the Bergen large-scale facility higher bacterial protein production (BPP), higher growth rates for particle-associated and free-living bacteria, as well as higher bacterial biomass but not abundance have been reported under high CO 2 (Grossart et al, 2006;Paulino et al, 2008;de Kluijver et al, 2010), in two similar experiments at the same site, no significant changes in bacterial abundance or activity could be observed Newbold et al, 2012). Apart from some minor differences in experimental design, these differences in the response of bacterioplankton activity were possibly due to differences in initial limitation of the bacterial community, as noted by Riebesell et al (2008).…”
Section: Introductionmentioning
confidence: 99%